2014
DOI: 10.1002/prp2.99
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in aryl N‐acetyltransferase results in significant differences in the pharmacokinetic and safety profiles of amifampridine (3,4‐diaminopyridine) phosphate

Abstract: The clinical use of amifampridine phosphate for neuromuscular junction disorders is increasing. The metabolism of amifampridine occurs via polymorphic aryl N-acetyltransferase (NAT), yet its pharmacokinetic (PK) and safety profiles, as influenced by this enzyme system, have not been investigated. The objective of this study was to assess the effect of NAT phenotype and genotype on the PK and safety profiles of amifampridine in healthy volunteers (N = 26). A caffeine challenge test and NAT2 genotyping were used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(40 citation statements)
references
References 31 publications
0
39
1
Order By: Relevance
“…Additional covariates, such as age, gender, and genotype status, were tested and not found to be significant covariates in this population. In a previous study, NAT2 genotype was reported to play a role in the PK profile of 3,4‐DAP phosphate . In our study, genotype status was available for a limited number of patients (11/49) and this may explain the lack of an association in this study.…”
Section: Discussionmentioning
confidence: 76%
See 4 more Smart Citations
“…Additional covariates, such as age, gender, and genotype status, were tested and not found to be significant covariates in this population. In a previous study, NAT2 genotype was reported to play a role in the PK profile of 3,4‐DAP phosphate . In our study, genotype status was available for a limited number of patients (11/49) and this may explain the lack of an association in this study.…”
Section: Discussionmentioning
confidence: 76%
“…We found that the parameter estimates using both the methods were similar, which is consistent with the limited number of BQL samples in our data set (26 samples (2% of total samples)). Similarly, given that the majority of 3,4‐DAP is converted to 3‐Ac DAP, we fixed the F m to 1, but also compared our results with fixing F m to 0.81 based on previous findings and incorporating an additional clearance route . Based on the results, the population estimates and range of individual EBEs for PK/PD parameters, as well as the diagnostic plots and OFV, were comparable between the two models.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations